Associations between β-blockers and psychiatric and behavioural outcomes: a population-based cohort study of 1.4 million individuals in Sweden - Molero, Y; Kaddoura, S; Kuja-Halkola, R; Larsson, H; Lichtenstein, P; D'Onofrio, BM; Fazel, S (Public Library of Science, 2023)
Background β-blockers are widely used for treating cardiac conditions and are suggested for the treatment of anxiety and aggression, although research is conflicting and limited by methodological problems. In addition, β-blockers have been associated with precipitating other psychiatric disorders and suicidal behaviour, but findings are mixed. We aimed to examine associations between β-blockers and psychiatric and behavioural outcomes in a large population-based cohort in Sweden.